Internal, External and Bilateral factors associated with desertion in university students - Zavala-Guirado, Martha (2018)
Taking into account twelve indices of factors associated with desertion in university students, a hypothetical model of internal, external and bilateral factors was tested, based on data from a sample consisting of 359 students from a public university in northwestern Mexico. Exploratory and confirmatory factorial analyzes suggested the structuring of three main factors associated with dropout, which agrees with the theoretical model proposed by the authors: 1. Internal Student Factors (ISF), 2. External Student Factors (ESF), and 3. Bilateral Factors (BF). A good divergent and convergent validity of constructs were obtained, with significant parameters for p <0.001, likewise, a confirmatory model with good goodness of fit was obtained (X2 = = 151.94; p = .00001; CFI = .91; RMSEA = .089). However, the factorial structure has slight variations in terms of its components previously specified in the theoretical model, an aspect that will be analyzed in the discussion.